PERIODICITY OF DECISIONS OF SOME SYSTEM OF TWO NONLINEAR DIFFERENTIAL EQUALIZATIONS OF THE SECOND ORDER - Краснодембський, Адам Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article there are the set terms of coincide of sequences, which determine the upshots with the nonlinear components of some system of two nonlinear differential equalizations of the second order